THE RESULTS OF PROFESSIONAL APPROACH AND INCREASED INTENSITY OF WORK - Georgi Georgiev; Viktor Mitrevski; Fadil Nika; Hasmir Hasani (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: The goal of the research is to establish if the professional approach and increased intensity of applied results in improvements and differences between the functional and motoric abilities (skills and habits) with students. Methods: The research has been conducted on a sample of 76 students at the age of 14. The first subsample consists of 40 students, and the second of 36 students, who, along with their regular school classes of 3 times a week and additional sports subject as choice (this refers to the first subsample as well), had regular trainings in basketball clubs three hours a week. They were tested by three indexes: 1) motoric abilities; 2) motoric skills and habits (Majeric, 2004); and 3) functional abilities (Jovanovic, 1999). There were calculated: basic descriptive statistic parameters, t-tests of independent samples, analysis of variance and Friedman test (Bala, 1986). Results: The results of the analyses are represented in 8 tables. On the base of the obtained results, the conclusion is that better results in all three indexes, are determined with the second subsample. It is those who are involved in regular school classes, have the sport as their additional subject choice, and had an active training work in their sports clubs. Discussion: The authors general conclusion of the research is that the number of that kind of research approach is quite small The results of the analyses of the first index in the conducted research show great similarity with the results obtained in the research of Georgiev, Kostovski, & Mitrevski (2012). The results of the second index indicate great similarity with Mitrevski's research (2012). The results of the third index are logically sustained. They are better with the second subsample. References: Bala G (1986). Logicke osnove metoda za analizu podataka iz istrazivanja u fizickoj kulturi. Novi Sad, Sava Muncan. Georgiev G, Kostovski Z, Mitrevski V (2012). Sport Mont, 34-36, 105-9. Jovanovic G (1999). Pulsometri u praksi. Bones, Kotor. Majeric М (2004). Analiza modelov ocenivanja sportnih znanj pri sportni vzgoji (Doktorska disertacija), Univerza v Ljubljani, Fakulteta za sport Ljubljana. Mitrevski V (2012). Razliki vo postiganjata i rezultatite po predmetot fizičko vospituvanje i obrazovanie i sport kaj učenicite od nekoi Balkanski državi (Doktorska disertacija), Univerzitet "Sv. Kiril i Metodij", Fakultet za fizička kultura, Skopje.